Difficulties in providing support services for female students with intellectual disabilities from the point of view of intellectual education teachers in Buraydah city - Al Bin Hamad, Salma Abdulrahman (Journal of Educational and Psychological Sciences, 2023)
The purpose of this study was to identify the difficulties intellectual education teachers in Buraidah City confront in providing supportive services. The descriptive approach was used to meet the purpose of the study. The study population consisted of 134 individuals, and the sample size was 115. The researcher used a questionnaire designed to identify the difficulties that hinder providing supportive services. The results indicated a consensus among the participants regarding the difficulties that prevent the provision of supportive services for students with intellectual disabilities in inclusive programs in Buraidah City. The diagnostic tools-based difficulties ranked first, followed by those related to the school environment. School administration-based difficulties ranked third, and finally, those associated with the multidisciplinary team were found to be the least hindering factor. The results also revealed statistically significant variations at a significance level of 0.05 between the means of participants' responses regarding the total score of difficulties that hinder the provision of supportive services for students with intellectual disabilities in inclusive programs and their sub-dimensions (school administration, school environment, and the diagnostic tools) based on the variation in the academic qualification variable with higher rates for holders of bachelor's degrees.
Keywords: difficulties; intellectual education teachers; students with intellectual disabilities; supportive services